Land use change on US floodplain buyout sites, 1990-2000 - Zavar, Elyse; Hagelman, III, Ronald R. (Disaster Prevention and Management, 2016)
Purpose - The Federal Emergency Management Agency provides guidelines for the management of open space created through property acquisition (buyouts); however, land use decisions are primarily left to local governments manifesting in a variety of uses. The purpose of this paper is to provide a land use assessment of buyout sites, to describe the changes in those uses that have occurred during a ten-year period from 1990 to 2000, and to offer an assessment of management approaches employed across these sites. Design/methodology/approach - Using a mixed-methods approach consisting of a land use classification survey and a semi-structured questionnaire of floodplain managers, this study explores the land use trends at buyout sites, diverse approaches local governments take in managing the open spaces created through floodplain buyout programs, and the successes and challenges communities face in open space management. Findings - Results indicate strong support from floodplain managers for property acquisition and several cases emerged where communities put their newly acquired public land to creative uses. However, the opportunity to leverage these properties for greater public values is largely being missed, primarily because of limited funding. Practical implications - The analysis indicates strong support among floodplain managers for the buyout approach; however, additional resource-sharing and funding opportunities are needed to increase the utility of buyout properties. Originality/value - By evaluating the long-term management strategies floodplain managers utilize on buyout sites, this study adds to an underrepresented area of scholarship and is of value to practitioners, government officials, and academics.
44 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/088-423-912-140-83X tex.eissn: [object Object] tex.orcid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: Buyout; Disaster mitigation; Floodplain management; Land use; dept.egm

Land-use change at temporary group-housing sites in post-Katrina Louisiana - Zavar, Elyse; Hagelman, III, Ronald; Lavy, Brendan; Prince, Benjamin (Natural Hazards Review, 2017)
To shelter the large number of displaced households following Hurricane Katrina (2005), FEMA, in conjunction with local governments, established 110 temporary group-housing sites throughout impacted Louisiana. The purpose of this study is to identify how temporary group-housing sites influenced the land use of post-Katrina Louisiana. Using aerial imagery, this study assessed the land use of each temporary group-housing site prior to Hurricane Katrina in 2005 and again in 2010. Of the 110 group-housing sites, 54.5% reverted to the previous land use, 29.1% returned to the previous land use with improvements, and 16.3% of the sites changed land use. Using census data from 2000 and 2010, site characteristics, and property records, this study employed a multinomial logistic regression to identify statistically significant variables in predicting land-use change in post-Katrina Louisiana. The results indicate that, especially in neighborhoods with high demand for land, FEMA temporary group-housing sites tended to be redeveloped into new land uses.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/146-296-911-884-194 tex.article-number: [object Object] tex.eissn: [object Object] tex.orcid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: Aerial imagery; Aerial photography; Group housing; Housing; Hurricane Katrina; Hurricane Katrina 2005; Hurricane katrina; Hurricanes; Land use; Land-use change; Local government; Louisiana; Multinomial logistic regression; Population statistics; Significant variables; Site characteristics; Temporary group housing; United States; aerial photograph; census; dept.egm; hazard assessment; hazard management; housing project; land use change; local government; neighborhood